Deteriorated sleep quality does not explain the negative impact of smartphone use on academic performance - Simon Amez; Sunčica Vujić; Margo Abrath; Stijn Baert (Global Labor Organization (GLO), 2021)
University students' smartphone use has recently been shown to negatively affect their academic performance. Surprisingly, research testing the empirical validity of potential mechanisms underlying this relationship is very limited. In particular, indirect effects of negative health consequences due to heavy smartphone use have never been investigated. To fill this gap, we investigate, for the first time, whether deteriorated sleep quality drives the negative impact on academic performance. To this end, we examine longitudinal data on 1,635 students at two major Belgian universities. Based on a combination of a random effects approach and seemingly unrelated regression, we find no statistically significant mediating effect of sleep quality in the relationship between smartphone use and academic performance.
Keywords: I21; I23; J24; 330; smartphone use; academic performance; sleep quality; mediation analysis